TÚRKIY TIL BILIMINDE GENDER MÁSELESINIŃ ÚYRENILIWI - Qosnazarova, U.; Allambergenova, G. (SCIENCE and SOCIETY, 2025)
Although the gender question is a new field in linguistics, it has developed quite rapidly and has become the object of special research. Gender studies took a special place in linguistics, and an independent linguistic field emerged - gender linguistics or linguistic genderology. In Turkic linguistics, the concept of gender has been sufficiently studied and more extensively researched in the linguistic direction. This article discussed the study of gender issues in Turkic languages, as well as the first manifestations of gender research in Karakalpak linguistics.